A new reciprocal linkage for expandable emergency structures. (December 2020) - Pérez-Valcárcel, J.; Suárez-Riestra, F.; Muñoz-Vidal, M.; López-César, I.; Freire-Tellado, M.J.
Abstract: Expandable structures have certain qualities in terms of lightness and transportability which make them very useful as emergency buildings, a research line that is being developed by the authors. However, these structures have some disadvantages due to their reduced rigidity and great deformability, issues that could limit their use. This paper analyzes a reciprocal linkage that considerably improves one of the main problems of expandable structures, which is their lack of rigidity. The extremely strict geometrical conditions for this proposed linkage and the mechanical behaviour are examined. Two series of tests were carried out, with specimens formed by four bars supported reciprocally around the proposed linkage. In the first case, the bars had their ends simply resting on the base and in the second one displacement was restricted at their ends. Theoretical analysis and the experimental tests results are also included. The tests make it possible to define the failure patterns of the different elements of the linkages, bars or bolts. The theoretical models and the experimental results show that the proposed reciprocal linkages are highly effective. Tests of plane scissor meshes were also carried out using reciprocal linkages, showing a very significant reduction in their displacements.